A Successful Endodontic Outcome with Non-Obturated Canals - Asgary, Saeed; Fazlyab, Mahta (Iranian Endodontic Journal, 2015)
This case report represents the outcome of endodontic treatment in an infected mandibular molar with periradicular periodontitis and inherent poor prognosis of root canal treatment due to severe root curvature. The tooth was successfully treated by leaving the mesial root non-obturated, the canal orifices were coronally sealed with calcium enriched mixture cement and a definitive coronal amalgam restoration, was placed at the subsequent visit. Keywords: Biomaterials; Calcium-Enriched Mixture; CEM Cement; Coronal Seal; Endodontics; SealBio; Root-End Surgery